2020
DOI: 10.1016/j.jsp.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of teacher-student relationships and longitudinal associations with children's conduct problems from Grades 1 to 12

Abstract: This study examined the development and continuity of teacher-student relationship quality across the formal schooling years (grades 1 to 12) and investigated how variations (i.e., differential trajectories) in teacher-student relationship quality were longitudinally associated with children's conduct problems across childhood and adolescence. Participants consisted of 784 students (M age = 6.57 in grade 1; 47% girls, 37.4% Latino or Hispanic, 34.1% European American, and 23.2% African American) who were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 70 publications
(123 reference statements)
2
17
0
2
Order By: Relevance
“…That is, for children with higher levels of interpersonal trust, they have better teacher–student relationships and social adjustment. This result was in line with the attachment theory and verified the previous findings ( Bowlby, 1980 ; Pianta et al, 1995 ; Rotenberg et al, 2005a ; Baker et al, 2008 ; Rotenberg, 2010 ; Liu et al, 2015 ; Ang et al, 2020 ; Ettekal and Shi, 2020 ). Therefore, hypothesis 1 failed to reject.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…That is, for children with higher levels of interpersonal trust, they have better teacher–student relationships and social adjustment. This result was in line with the attachment theory and verified the previous findings ( Bowlby, 1980 ; Pianta et al, 1995 ; Rotenberg et al, 2005a ; Baker et al, 2008 ; Rotenberg, 2010 ; Liu et al, 2015 ; Ang et al, 2020 ; Ettekal and Shi, 2020 ). Therefore, hypothesis 1 failed to reject.…”
Section: Discussionsupporting
confidence: 92%
“…A teacher plays a vital role in children’s school years ( Pianta et al, 1995 ; Ettekal and Shi, 2020 ). On the basis of attachment theory, positive teacher–student relationships in childhood may provide children with security and enhance their adjustment to school ( Bowlby, 1980 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be the case that preexisting problem behaviors contributed to some of the difficulties children experienced by the time they entered Grade 1 (Wiggins et al, 2015). For instance, teacher-child conflict can also increase due to existing problem behaviors (Ettekal & Shi, in press), potentially leading to a maladaptive cycle. Fourth, future studies can further examine the heterogeneity of internalizing and externalizing problems at a higher-order-level.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of teacher-student relationships in student academic and social development has been well established (Ansari, Hofkens, and Pianta 2020;Ettekal and Shi 2020;Quin 2017). Allen et al (2013) found that teachers' ability to respond sensitively to student needs was directly linked to student achievement: 'students first and foremost are highly social and emotional beings.'…”
Section: Introductionmentioning
confidence: 99%